Correlation between Meaningful Work and Employee Job Crafting with Mediator Work Engagement - Chanafi, Alfi Rossi; Yudiarso, Ananta (Jurnal Sains Psikologi, 2023)
This research was conducted to examine the correlation between meaningful work on job crafting with work engagement mediators. The inconsistency of results in several previous studies is why this research is being conducted. The type of research used is correlational quantitative with survey methods. This study uses three measurement tools: the Work as Meaning Inventory to measure meaningful work, the Utrecht Work Engagement Scale to measure work engagement, and the Job Crafting Scale. The form of research analysis uses Rasch Model analysis and Multilevel Structural Equation Modeling. Data obtained from 107 employees with minimum age criteria of 18 years, who have worked for at least three months, and are active employees in the formal sector, specifically in private companies, show that indirectly effect there is a significant correlation (p less than or equal to 0.001) on meaningful work towards job crafting through work engagement. The results of this study mean that employees who can interpret their work are supported by a totality level of enthusiasm for work so that they can design their work with their proactive strategy. Suggestions for future research are to explore the scope of research participants in state-owned companies to obtain research results with a more comprehensive picture.